Photobiomodulation therapy for acute radiodermatitis. Issue 4 (July 2019) - Robijns, Jolien; Lodewijckx, Joy; Mebis, Jeroen
Abstract : Purpose of review: The number of clinical trials on the use of photobiomodulation therapy (PBMT) for the management of cancer therapy-related complications is growing steadily. One of the side-effects that is under investigation is acute radiodermatitis (ARD), an inflammatory skin reaction caused by radiotherapy. In this review, an overview is given on the state of art of the application of PBMT for the prevention and management of ARD. Recent findings: Up to now about seven clinical trials have been performed, investigating the use of PBMT in the prevention and/or management of ARD. Results demonstrate that PBMT can effectively reduce the incidence of severe ARD, decrease the accompanying pain, and improve the patients' quality of life. Moreover, the technique seems to be well tolerated in oncologic patients. Summary: On the basis of the available evidence, there could be a strong recommendation to use PBMT in the prevention and management of ARD in cancer patients.